(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
ENTER. Today, the social and economic development of the country is being achieved under the slogan "New Uzbekistan - Towards the Third Renaissance". In this sense, any event, concept or term has its own formation process. The phenomenon of New Uzbekistan is no exception. This concept expresses the basic idea of ​​our reforms to form the modern image of our country, establish a democratic state, a free civil society in our country, and create the foundations of the Third Renaissance.